2010
DOI: 10.1002/jat.1619
|View full text |Cite
|
Sign up to set email alerts
|

Sequential measurements of glomerular filtration rate in conscious rats by a bolus injection of iodixanol and a single blood sample

Abstract: To estimate the glomerular filtration rate (GFR) sequentially in conscious rats, we validated a single-blood-sample method using a bolus injection of the nonionic contrast medium iodixanol as a tracer. First, to clarify basal age-related GFR profiles, iodixanol was intravenously administered once weekly at 1500 mg kg(-1) I to clinically healthy male F344 rats from 6 to 15 weeks of age. The blood sample was collected 120 min later, and serum iodixanol concentration was measured by HPLC. GFR values decreased gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Cisplatin was administered intraperitoneally at 45 mg/m 2 , corresponding to 7.5 mg/kg (FDA-CDER Guidance 2005), to groups of six 8-week-old SD rats, as described in our previous reports. 31,32) Our previous studies indicated that intraperitoneally administration of cisplatin at 22.5 mg/m 2 slightly induced nephrotoxicity. We also found that administration of cisplatin at 45 mg/m 2 moderately induced the nephrotoxicity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin was administered intraperitoneally at 45 mg/m 2 , corresponding to 7.5 mg/kg (FDA-CDER Guidance 2005), to groups of six 8-week-old SD rats, as described in our previous reports. 31,32) Our previous studies indicated that intraperitoneally administration of cisplatin at 22.5 mg/m 2 slightly induced nephrotoxicity. We also found that administration of cisplatin at 45 mg/m 2 moderately induced the nephrotoxicity.…”
Section: Methodsmentioning
confidence: 99%
“…We noted marked increases in SUN and CRE with decreased body weight and extensive tubular necrosis, loss of the epithelial brush-border, pyknosis in the renal proximal epithelia, and the presence of cysts in the lumen on day 5, as found previously. 31,32) Renal mitochondrial GOT and MDH activities in cisplatin-induced nephrotoxicity…”
Section: Cisplatin-induced Nephrotoxicity In Ratsmentioning
confidence: 99%
“…; Levey ; Katayama et al. ). Despite their limitations, endogenous biomarkers of kidney function, such as creatinine and urea, are widely used to evaluate kidney function in experimental models.…”
Section: Introductionmentioning
confidence: 99%